Rehabilitating form, function and natural aesthetics with Onlay Ceramic IPS Empress Esthetic® : evidence and versatility = Rehabilitando forma, función y estética mediante el uso de un Onlay IPS Empress Esthetic® : evidencia y versatilidad - Ramírez Barrantes, Juan Carlos 1964-
Clinical research and in vitro laboratory tests have enabled the development and improvement of dental ceramics. Comprehension of the physical and mechanical properties of this material is essential, in order to ensure a functional, aesthetic and long-lasting posterior ceramic restoration. The clinical protocol for onlay preparation involves important considerations in treatment planning, such as selection of the restorative material, biomechanical design, color selection, dental substrates conditioning and adhesive cementation. This article discusses a brief review on the topic and a case presentation in which a posterior tooth was rehabilitated with an IPS Empress Esthetic® ceramic onlay.